Powtoon Learning Media Contextually Based on Thermochemistry Materials to Increase Students' Learning Motivation - Azizah, Nur; Kamaludin, Agus (Indonesian Journal of Science and Mathematics Education, 2023)
Thermokinetics material is a conceptual and abstract topic in chemistry. Therefore, instructional media is needed to make thermokinetics more tangible to enhance student motivation in learning chemistry. The objective of this research is to develop a contextual-based instructional medium using Powtoon for thermokinetics and determine the quality of the developed product. The research method employed is Research and Development, adapting the 4-D model (Definition, Design, Development, and Dissemination). Research instruments include a product quality assessment sheet and a student response sheet. Based on evaluations by subject matter experts, media experts, and chemistry educators/reviewers, the percentages obtained are 93%, 95%, and 90%, respectively, belonging to the "excellent" category. Students responded positively to the video, achieving an ideal percentage of 90%, also categorized as "excellent." Thus, the developed product is deemed suitable as an alternative medium in thermokinetics learning to boost student motivation. For future research, it is recommended to measure the effectiveness of instructional media on student learning outcomes.